Rancang Bangun Alat Hand Wash Menggunakan Handle Feet Otomatis Di Puskesmas Fakfak Kota Kabupaten Fakfak - Rusdin Rusdin (Pengelola Jurnal Politeknik Negeri Ketapang, 2021)
Covid-19 is a collection of viruses that can infect the respiratory system. In many cases, this virus only causes mild respiratory infections, such as flu. However, this virus can also cause severe respiratory infections, such as lung infections (pneumonia). Hand sanitizer is a hand sanitizer in the form of a gel that is useful for cleaning or removing germs on the hands, containing 60% alcohol as the active ingredient. Automatic handle feet are a component part of the tool that functions as a water valve opening lever and is also equipped with a peges so that the lever will return to its original position, while the Puskesmas Office is a government agency in the health sector that is used as a Community Partnership Program (PKM) partner.